whisky jacks (1970)
whisky jacks . and the 'whisky jacks,' who had not shown themselves for several days, appeared again with their shrill cries, venturing impudently into the very door of our tent to claim scraps of refuse. PRINTED ITEM G.M. Story AUG 1970 JH AUG 1970 Not used Not used Withdrawn withdrawn but no stamp